An Analysis of Phrasal Verb on English Subtitle Avengers: Endgame Movie (A Study of Written Discourse Analysis) - Elim Trika Sudarsi; Jevika Dianita Kole; Rachel Rachel (Departement of Mathematics Education, 2023)
The objective of this research is to find out the kinds of phrasal verbs found in English subtitles in the Avengers: Endgame movie. The writer used qualitative methods in this study. The data was taken from the film transcript Avengers: Endgame. The data that had been collected was analyzed using Foucalt's theory.The results of this study indicate that there are two kinds of phrasal verbs that appear in the English subtitles Avengers: Endgame movie, namely intransitive phrasal verbs and transitive phrasal verbs (separable transitive phrasal verb and inseparable transitive phrasal verb). In this study, the writer analyze the phrasal verbs that appear by taking into account the situational context, the context of background knowledge and the co-textual context.